Determinants of Entrepreneurial Interest among Vocational High School Students in Business Management in Semarang City - Zahro, Iqbalina; Rusdarti, Rusdarti; Widiyanto, Widiyanto (Universitas Negeri Semarang, 2024)
Entrepreneurial interest is the desire, motivation, and drive to interact and do everything with enthusiasm to achieve goals by working hard, and opening opportunities with skills and confidence. This study aims to analyze the entrepreneurial interest of vocational high school students and identify factors influencing entrepreneurial interest, including entrepreneurial knowledge, family environment, and industrial work practice. The results show that entrepreneurial knowledge positively influences self-efficacy, the family environment positively influences self-efficacy, and industrial work practice influences self-efficacy. The total effect of entrepreneurial knowledge on entrepreneurial interest through self-efficacy is 19.27%, the family environment on entrepreneurial interest through self-efficacy is 56.68%, industrial work practice on entrepreneurial interest through self-efficacy is 14.46%, and self-efficacy positively affects entrepreneurial interest by 38.07%. Sobel's test results show that self-efficacy is a mediating variable. The results indicate that all independent variables studied have a positive and significant influence on the entrepreneurial interest of students at State Vocational High Schools in Business and Management in Semarang City